Vitiligo and surgical treatment - Tran, Van Anh; Vu, Quang Vinh (Tạp chí Y học Thảm hoạ và Bỏng, 2023)
Objective: Initial comments on the effectiveness of surgical treatment of vitiligoResearch subjects and methods: A prospective study on 12 cases of vitiligo that were successfully treated with autologous pigment cell transplant surgery. Research period from September 2018 to October 2022 at the Center for Plastic Surgery, Surgery & Regeneration - Le Huu Trac National Burn HospitalResults: 12 patients with an average age of 29, with vitiligo in several locations on the body, received pigment-containing cell transplant surgery. The graft adheres well, ensuring good coverage and assimilating the color of the vitiligo skin area with the surrounding healthy skin after about 12 months.Conclusion: Pigment graft surgery is one of the effective methods of treating vitiligo and can be applied to large areas of the diseased skin.